Cassava seeds standard launched in Rwanda - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
IITA Rwanda in partnership with the Rwanda Agriculture and Animal Resource Development Board (RAB) and Rwanda Standard Board (RSB) launched the Cassava Seeds Standards under an IITA project; Cassava Brown Streak Disease Control Project. The standards will help control and deliver quality seeds to cassava farmers in Rwanda.